POTENSI DESA PINGE SEBAGAI DESA WISATA DI KECAMATAN MARGA, KABUPATEN TABANAN - Tabing Geovani; ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2014)
Abstract Pinge Tourism Village is a village in Marga Tabanan. The aim of the research is to describe the potency of Pinge tourism village at Tabanan. The method of this research is qualitative method with the descriptive approach. Data is collected by observation and documentation. In this research the method is determined by purposive sampling that researchers choose informants according to certain predetermined criteria. The results of this research indicates, the Pinge tourism village is very potential to develop that there are still natural object,unique tradition and use for tourist education about the rural social life farming etc. This Village is in prosses to development tourism in basic village and general purpose for Pinge people prosperity. As result of research in this village make decision that this village able to be success in the future if the system able running better and all people can be a good teamwork. This village also needs more support by all component exactly government in Tabanan. Pinge exactly has a great potension because this village has made many aspects like accommodation, facilities, accessibility, and otherinfrastructur.